2022
DOI: 10.1021/acs.jpcb.2c00634
|View full text |Cite
|
Sign up to set email alerts
|

Study on Excited State Kinetics and Optical Limiting Performance of Triphenylamine-Based Chalcone Derivatives: Effect of the Molecular π-Conjugated Structure

Abstract: Optical limiting (OL) is an important application of nonlinear optics. Summarizing the structure–property relationship of organic materials is an effective means to develop superior optical limiters. In this work, two triphenylamine-based chalcone derivatives T1 and T2 with different peripheral substituent groups were synthesized to study their transient kinetics and nonlinear optical (NLO) absorption performance. The transient absorption spectrum (TAS) of compounds T1 and T2 in solvents of varying polarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…20 Targeted improvement of NLO absorption properties such as TPA and excited-state absorption (ESA) based on structure-property relationships is the key to the development of organic OL materials. 21 Numerous studies in the literature have suggested that the reverse saturable absorption (RSA) properties of organic materials can be improved by modulating the electron push-pull system and the molecular p-conjugated structure. [22][23][24][25] However, the majority of studies have not elucidated the effects of intramolecular charge transfer (ICT) and p-electron delocalization on TPA or ESA.…”
Section: Introductionmentioning
confidence: 99%
“…20 Targeted improvement of NLO absorption properties such as TPA and excited-state absorption (ESA) based on structure-property relationships is the key to the development of organic OL materials. 21 Numerous studies in the literature have suggested that the reverse saturable absorption (RSA) properties of organic materials can be improved by modulating the electron push-pull system and the molecular p-conjugated structure. [22][23][24][25] However, the majority of studies have not elucidated the effects of intramolecular charge transfer (ICT) and p-electron delocalization on TPA or ESA.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the smallest twistacene is 9,14-diphenyldibenzo­[ de , qr ]­tetracene, which can be regarded as an electron-rich motif. In general, the sp-hybridized alkyne bond is a covalent bond linker, which can not only promote molecular coplanarity but also increase the π–π* transition within the molecules. , When the alkyne group is connected with the twistacene, the as-formed derivatives might possess excellent solubility in organic solvents, enhanced charge transfer, and broadband optical limiting ability. Although many derivatives resulting from such twistacenes with positive nonlinear optical responses have been prepared, systematic examination of the effect of the connection mode of alkyne bonds on the nonlinear optical performance and absorption mechanism is unprecedented.…”
Section: Introductionmentioning
confidence: 99%